1996
DOI: 10.1159/000134439
|View full text |Cite
|
Sign up to set email alerts
|

3p21 is a recurrent treatment-related breakpoint in myelodysplastic syndrome and acute myeloid leukemia

Abstract: In this study we report 11 cases with chromosome abnormalities involving 3p21. Nine cases were diagnosed as myelodysplastic syndrome (MDS), and two as acute myeloid leukemia (AML). Six of nine MDS cases were secondary to a primary malignant disease. In two patients, AML was secondary to breast cancer and polycythemia vera (PV). Seven of eleven patients had a history of intensive polychemotherapy and/or radiation therapy for 3.5 to 5 years. The mean interval from initial therapy to secondary disease was 13.2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The Pyst2-L gene is located on the 3p21 chromosomal region. Aberrations within this area have been previously described to occur in various types of malignancies (Shi et al, 1996;Johnson et al, 2000;Sano et al, 2000). However, the results presented above showed that no aberration, amplification or point mutations occurred in the Pyst2-L DNA of leukemic cells.…”
Section: Discussionmentioning
confidence: 86%
“…The Pyst2-L gene is located on the 3p21 chromosomal region. Aberrations within this area have been previously described to occur in various types of malignancies (Shi et al, 1996;Johnson et al, 2000;Sano et al, 2000). However, the results presented above showed that no aberration, amplification or point mutations occurred in the Pyst2-L DNA of leukemic cells.…”
Section: Discussionmentioning
confidence: 86%
“…[35][36][37][38][39][40] The finding that the 3p deletions in both AML and MDS frequently occurred together with del(5q) and frequencies in the chronic lymphoproliferative disorders and the lymphomas than in the chronic myeloid disorders and the monosomies for chromosomes 5 and 7 -well known therapyassociated abnormalities in these disorders 26 -provides acute leukemias. In general, the incidences of 3p deletions did not differ among the morphologic subgroups of the hemafurther evidence in favor of 3p loss as a treatment-related abnormality.…”
Section: Figurementioning
confidence: 99%
“…Overexpression of H37/Luca15/RBM5 has been demonstrated to result in cell cycle arrest and apoptosis in human lung carcinoma (22). Deletions or translocations involving 3p21 have been linked to acute leukemia, myelodysplastic syndrome and solid tumor types, including small cell lung and renal cell carcinomas (21,23,24).…”
Section: Discussionmentioning
confidence: 99%